2011
DOI: 10.3109/10520295.2011.570276
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of MUC1, MUC2 and CK17 expression patterns for diagnosis of pancreatobiliary arcinoma

Abstract: Pancreatic cancer is characterized by aggressive growth and resistance to treatment. Identification of unique biomarkers for diagnosis and prognosis is important for treatment of this disease. We investigated the expression patterns of mucin 1 (MUC1), mucin 2 (MUC2) and cytokeratin 17 (CK17) in both normal tissues and metastatic adenocarcinomas using immunohistochemistry (IHC). We have shown that MUC1 (pan-epithelial membrane mucin), MUC2 (intestinal-type secretory mucin) and CK17 can be used as a panel of mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…CK17 is a low-molecular-weight keratin that is normally expressed in myoepithelial and basal cells and subsets of hair shaft epithelia [13]. A few studies have demonstrated it to be of value in the distinction between pancreaticobiliary and nonpancreaticobiliary adenocarcinomas [13,16,30,31]. In accordance with published results, our data showed frequent CK17 expression in PDAs, seen in 60% of the cases.…”
Section: Discussionsupporting
confidence: 90%
“…CK17 is a low-molecular-weight keratin that is normally expressed in myoepithelial and basal cells and subsets of hair shaft epithelia [13]. A few studies have demonstrated it to be of value in the distinction between pancreaticobiliary and nonpancreaticobiliary adenocarcinomas [13,16,30,31]. In accordance with published results, our data showed frequent CK17 expression in PDAs, seen in 60% of the cases.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we determined that K17 status is as a better negative prognostic marker than p27 KIP1 and tumor stage. We previously identified K17 as a candidate cervical cancer biomarker by proteomic analysis of normal cervical mucosa, cervical intraepithelial neoplasia, and cervical squamous cell carcinoma, and other reports have suggested that K17 expression may be overexpressed in pancreatic, urothelial, colorectal, and head and neck carcinomas (5,(36)(37)(38). Thus, these prior observations, together with our current in vitro and in vivo data, suggest that K17 expression could in fact be involved in oncogenic signaling of a wide range of cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Keratin 17 (K17), although not present in normal mature epithelia, is expressed in stem cells of embryonic ectoderm, skin appendages, and the endocervical mucosa, and it is re-expressed in carcinomas (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that MUC expression is involved in the invasion and metastasis of various malignancies, including gallbladder cancer [19], breast cancer [20], ovarian cancer [21], gastric carcinoma [22,23], pancreatic carcinoma [24][25][26], ampullary cancer [27,28], lung cancer [16,29], prostate cancer [30], renal cell carcinoma [31], and appendiceal carcinoma [32]. However, the prognostic value of MUC expression in CRC remains controversial [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%